Can India universalize social insurance before its demographic dividend ends? The principles and architecture for universalizing social security by 2030 - Santosh K. Mehrotra (University of Bath, Centre for Development Studies (CDS), 2022)
As much as 91% of India's workforce of 475 million is informal, lacking social insurance. The latest effort on social security is India's Social Security Code 2020, which merges eight existing laws. The paper finds the Code wanting by comparing it with the principles that should guide social insurance for informal workers in India. Drawing on this analysis it then sets out proposals for what a social insurance system for India could look like. The roadmap to such reform is long drawn out and challenging given the size of the country, the immensity of its population, its diversity and the complexity of informality in the workforce. Nevertheless, the goal remains that over the next ten years, social insurance should cover the entire workforce, in accordance with ILO Conventions. The paper closes by estimating the fiscal cost of what is proposed, both to federal and state governments.
Keywords: 330; disability benefits; informal labour; maternity benefits; pensions; social insurance